Organoleptic Characteristics and Chemicals Ilabulo Catfish Fortification - Rita Marsuci Harmain; Faiza Dali; N. Nurjanah; Agoes Mardiono Jacoeb (Jurnal Pengolahan Hasil Perikanan Indonesia, 2017)
Diversification of traditional food ilabulo made from raw catfish (Pangasius sp.) has the potential to be developed in Gorontalo province to substitute chicken viscera. The research aimed to make ilabulo substitute the raw material of chicken viscera with the catfish fortified Kappaphycus alvarezii seaweed and catfish bone meal and to determine the organoleptic and chemical characteristics of ilabulo catfish fortification. Fortified treatment is K. alvarezii  and catfish bone (5 dan 10% ),  B (10 and 15%) and  C (15 dan 20%). The organoleptic analysis used a hedonic scale of favorite criteria on the appearance, texture, color, flavor, and taste. The results of organoleptic analysis continued with Bayes test. The chemical analysis used the Association of Official Analytical Chemist method. The result of the hedonic characteristic of ilabulo catfish fortification was on the appearance  neutral criteria – like (5.53–7.03), texture neutral criteria – rather like (5.8–7.1), aroma rather like (6.3–6.73), color neutral – like (6.1–7.03) and taste (6.07–6.53) neutral criteria – rather like. The result of Bayes test obtained by a texture of importance value 5, appearance importance value 5, aroma of importance value 4, color of interest value 3 and taste of importance value 2. Characteristic of ilabulo culture of selected fortified catfish that was the fortification of K. alvarezii seaweed 15% and catfish  bone flour (20%) (fortification C) obtained by water content 56.46%, ash 11.54%, protein 7.78%, fat 8.91%, coarse fiber 0.61%, carbohydrate 22.07% and calcium 0.315 %.